Observed use of voluntary controls to reduce physical exposures among sheet metal workers of the mechanical trade. (January 2016) - Dale, Ann Marie; Miller, Kim; Gardner, Bethany T.; Hwang, Ching-Ting; Evanoff, Bradley; Welch, Laura
Abstract: Introduction: Little is known about the transfer into the workplace of interventions designed to reduce the physical demands of sheet metal workers. Methods: We reviewed videos from a case series of 15 sheet metal worksite assessments performed in 2007–2009 to score postures and physical loads, and to observe the use of recommended interventions to reduce physical exposures in sheet metal activities made by a NIOSH stakeholder meeting in 2002. Results: Workers showed consistent use of material handling devices, but we observed few uses of recommended interventions to reduce exposures during overhead work. Workers spent large proportions of time in awkward shoulder elevation and low back rotation postures. Conclusions: In addition to the development of new technologies and system designs, increased adoption of existing tools and practices could reduce time spent in awkward postures and other risks for musculoskeletal disorders in sheet metal work. Highlights: Our observations showed incomplete transfer of trade-specific stakeholder recommendations into work practice. Tools and practices to reduce physical exposures among construction workers, a high risk group for MSD, are not fully adopted. More work is needed to disseminate means to reduce exposures in this decentralized industry with slow adoption of technology.